2020
DOI: 10.1038/s41598-020-62329-9
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantification of Photoreceptor alteration in macular disease using Optical Coherence Tomography and Deep Learning

Abstract: Diabetic macular edema (DME) and retina vein occlusion (RVO) are macular diseases in which central photoreceptors are affected due to pathological accumulation of fluid. Optical coherence tomography allows to visually assess and evaluate photoreceptor integrity, whose alteration has been observed as an important biomarker of both diseases. However, the manual quantification of this layered structure is challenging, tedious and time-consuming. In this paper we introduce a deep learning approach for automaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…According to a study, an ensemble scheme of four different CNNs was introduced to automatically segment and characterize photoreceptor alteration in macular disease. The results showed that the ensemble scheme outperformed each of its constitutive models with higher Dice coefficient, precision and sensitivity (39). Similarly, the accuracy of the prediction was performed by integrating the ensemble DL scheme and the ensemble CML scheme, which remained satisfactory according to the results of our study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…According to a study, an ensemble scheme of four different CNNs was introduced to automatically segment and characterize photoreceptor alteration in macular disease. The results showed that the ensemble scheme outperformed each of its constitutive models with higher Dice coefficient, precision and sensitivity (39). Similarly, the accuracy of the prediction was performed by integrating the ensemble DL scheme and the ensemble CML scheme, which remained satisfactory according to the results of our study.…”
Section: Discussionsupporting
confidence: 68%
“…The model automatically processed vital information (also called "features") for predicting the prognosis and generated the output of CFT and BCVA predictions based on the integration of the above features. Recent studies have shown that the ensemble scheme outperformed each individual alternative, improving the performance obtained by each characterization model separately (39,40). According to a study, an ensemble scheme of four different CNNs was introduced to automatically segment and characterize photoreceptor alteration in macular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The reference frame may also be applied to other study cohorts such as healthy versus various stages of AMD (mild, moderate, severe) 31 , 41 to obtain a broader view on disease progression. Furthermore, with the rapid development in AI and particular deep learning, more accurate and fine-grained segmentations will become available 5 , such as precise RPE and photoreceptor segmentations 42 , 43 , which may lead to novel findings and highlight different aspects of disease progression when analysing these in the proposed reference frame. A spatio-temporal atlas may also incorporate other OCT modalities such as adaptive optics OCT (AO-OCT), OCT angiography (OCT-A) or directional OCT (D-OCT) 35 that provide complementary information regarding the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…AI-algorithms for either the quantification of photoreceptor loss or preferably subclinical photoreceptor thinning might become important tools for the evaluation of treatment effects in various macular diseases. 62 , 65 , 66 …”
Section: Fluid Quantificationsmentioning
confidence: 99%